2014
DOI: 10.2147/ijn.s64301
|View full text |Cite
|
Sign up to set email alerts
|

Passing through the renal clearance barrier: toward ultrasmall sizes with stable ligands for potential clinical applications

Abstract: The use of nanoparticles holds promise for medical applications, such as X-ray imaging, photothermal therapy and radiotherapy. However, the in vivo toxicity of inorganic nanoparticles raises some concern regarding undesirable side effects which prevent their further medical application. Ultrasmall sub-5.5 nm particles can pass through the barrier for renal clearance, minimizing their toxicity. In this letter we address some recent interesting work regarding in vivo toxicity and renal clearance, and discuss the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Target-oriented differences in biodistribution -due to differences in the charges -could be observed, which indicated that positive Au NCs preferred to accumulate in the kidneys. [47][48][49] Additionally, higher retention in other RES organs such as liver and spleen at 1 day after administration indicate fast clearance from the bloodstream.…”
Section: Biodistribution and Excretionmentioning
confidence: 99%
“…Target-oriented differences in biodistribution -due to differences in the charges -could be observed, which indicated that positive Au NCs preferred to accumulate in the kidneys. [47][48][49] Additionally, higher retention in other RES organs such as liver and spleen at 1 day after administration indicate fast clearance from the bloodstream.…”
Section: Biodistribution and Excretionmentioning
confidence: 99%
“…Ideal nanomaterial should be effectively cleared out of the body, have little accumulation in organs. Sub-5.5 nm particles can pass through the barrier for renal clearance [50]. However, we need to know whether these particles still could pass through glomerulus when they are functioned by connecting with other molecules such as antibodies.…”
Section: Western Blotting and Immunohistochemistymentioning
confidence: 99%
“…Recent progresses in silicon carbide (SiC) crystal, film's synthesis [1][2][3][4][5][6][7][8][9][10], and investigations of nano-polytype properties are highly important for applications in harsh environments [11], in optoelectronics [12,13] and spintronics [14,15], in quantum information processing [16][17][18], in biotechnology [19,20] and medicine [21,22]. Silicon carbide [23] can be a suitable prototype material for investigations of the polytypism phenomena in wide band semiconductors and binary materials.…”
Section: Introductionmentioning
confidence: 99%